Top of the Mountain: The Beatles at Shea Stadium 1965 - Jacobson, Laurie (Rowman & Littlefield Publishers, 2022)
In August 1965, during a sweltering heatwave, 56,000 people traveled by plane, car, bus, ferry, and subway train to pack New York's Shea Stadium on a Sunday evening—not for a baseball game, but for a rock and roll concert. This idea was the crazy dream of concert promoter Sid Bernstein. No rock band had ever played a baseball stadium, and no one believed he could pull it off. But on that glorious night, The Beatles sold out Shea Stadium, shattering all existing box office and attendance records in show business history. Oh, and they also changed the world. Against the backdrop of a remarkably volatile year in our nation's history, Top of the Mountain: The Beatles at Shea Stadium, 1965 delivers all the detail and excitement of Shea and the spirited, curious new generation who would soon claim the decade for its own. Told through first-person interviews and quotes, a unique cast of characters tells the story: celebrities then and celebrities now, writers, agents, producers, photographers, opening act performers, fans, security guards, radio personalities, cameramen, and media—all of whom were part of the night. Caryn Johnson (Whoopi Goldberg) and Steven Lento (Little Steven Van Zandt); future Beatle wives Linda Eastman and Barbara Bach; established stars like Bobby Vinton and Ed Sullivan; and artists hoping one day to equal this success, such as Mick Jagger, Keith Richards, Felix Cavaliere and The Rascals, Marvin Gaye, and more share their memories of this remarkable night in Top of the Mountain.